Boletim Official do Governo da Provincia de Macau (IMPRENSA NACIONAL, 1903)
Stamp of St. Joseph Seminary
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Exposition du Dogme Catholique (P. Lethielleux, Libraire-Editeur, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 6.Yellowing 變黃; Fair

Exposition du Dogme Catholique (P. Lethielleux, Libraire-Editeur, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 6.Yellowing 變黃; Fair

Exposition du Dogme Catholique (P. Lethielleux, Libraire-Editeur, 1903)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Exposition du Dogme Catholique (P. Lethielleux, Libraire-Editeur, 1903)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

I. C. S. Reference Library (International Textbook Company, 1903)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Tragedia Antiga - Cesar Porto (Livraria Central, 1903)
Keywords: 2.Damage; Condition: Fair

Petit dictionnaire chinois-français - Couvreur, Séraphin (Imprimerie de la Mission catholique, 1903)
《法汉小字典》
Keywords: 18.Bookworm; China; Chinese language; Chinese language Dictionaries French; Chinois (langue) Dictionnaires français; Condition: Fair; Dictionaries; French language; French language Dictionaries Chinese; Hard Cover; Wörterbuch; languages

Carta Pastoral - D'AZEVEDO E CACTRO, D.JOAO PAULINO (Typographia do Seminario, 1903)
Keywords: Macau; Religion; USJ SEMINARY LIBRARY PROJECT

Recordacoes da Mina Peregrinacao, A Roma e Lourdes - Ferreira, Congo Antonio Maria (Typograph Fidelidade, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

El Impedimento de clandestinidad - Ferreres, Juan B. (Sucesores de Rivadeneyra, 1903)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Nul·litat del matrimoni

Theologia Dogmatie Moral-Explicacao Historica do Catecismo - Guillois, Abbade Ambrosio (Libraria Internacional, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Theologia Dogmatie Moral-Explicacao Historica do Catecismo - Guillois, Abbade Ambrosio (Libraria Internacional, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Catecismo: Explicação historica dogmatica, moral, liturgica e canonica do catecismo com a resposta ás objecções extrahidas das sciencias contra a religião - Guillois, Ambrosio (Livraria Chardron, 1903)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Religion

The principal navigations, voyages, traffiques & discoveries of the English nation - Hakluyt, Richard (Works issued by the Hakluyt Society, 1903)
Keywords: 10.Cover Damage; 22.stamp; Condition: Fair; Discoveries in geography English; Hard Cover; Travel; Voyages; Voyages and travels; journeys

The principal navigations, voyages, traffiques & discoveries of the English nation - Hakluyt, Richard (Works issued by the Hakluyt Society, 1903)
Keywords: 10.Cover Damage; 22.stamp; Condition: Fair; Discoveries in geography English; Hard Cover; Travel; Voyages; Voyages and travels; journeys

The principal navigations, voyages, traffiques & discoveries of the English nation - Hakluyt, Richard (Works issued by the Hakluyt Society, 1903)
Keywords: 10.Cover Damage; 22.stamp; Condition: Fair; Discoveries in geography English; Hard Cover; Travel; Voyages; Voyages and travels; journeys

Commentarius in Librum Iosue - Hummelauer, Francisco de (Summptibus P. Lethielleux, Editoris, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 6.Yellowing 變黃.

Theologiae Specialis - Hurter, H. (Libraria Academica Wagneriana, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Exposition du dogme catholique - J. M. L. Monsabré (Lethielleux, 1903)
Keywords: 2.Damage; 22.stamp; Condition: Fair; Religion

Exposition du Dogme Catholique - J. M. L. Monsabré (P. Lethielleux, 1903)
sign
Keywords: Good

exposition du Dogme Catholique - J. M. L. Monsabré (Conférences de Notre-Dame de Paris, 1903)
stamp of Bibliethéque de Nazareth
Keywords: Good

exposition du Dogme Catholique - J. M. L. Monsabré (Conférences de Notre-Dame de Paris, 1903)
stamp of Bibliethéque de Nazareth
Keywords: Good

exposition du Dogme Catholique - J. M. L. Monsabré (Conférences de Notre-Dame de Paris, 1903)
stamp of Bibliethéque de Nazareth
Keywords: Good

exposition du Dogme Catholique - J. M. L. Monsabré (Conférences de Notre-Dame de Paris, 1903)
stamp of Bibliethéque de Nazareth
Keywords: Good

Histoire des Dogmes - Joseph Schwane (Gabriel Beauchesne, 1903)
stamp of missions etrangeres no. 1, Battery Path Hong Kong
Keywords: 10.Cover Damage; Good

Histoire des Dogmes - Joseph Schwane (Gabriel Beauchesne, 1903)
stamp of missions etrangeres no. 1, Battery Path Hong Kong
Keywords: 10.Cover Damage; Good

Histoire des Dogmes - Joseph Schwane (Gabriel Beauchesne, 1903)
stamp of seminário de s. jose biblioteca, stamp of missions etrangeres no. 1, Battery Path Hong Kong
Keywords: 10.Cover Damage; 18.Bookworm; Good

A Mulher, na Escola De Maria - Larfeuil, Abbade (Livararia Povoense, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Casus Conscientiae ad Usum Confessariorum Compositi et Soluti - Lehmkuhl, Augustino (Sumptibus Herder, 1903)
Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Casus Conscientiae ad Usum Confessariorum Compositi et Soluti - Lehmkuhl, Augustino (Sumptibus Herder, 1903)
Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Exposition du dogme catholique: grace de Jésus-Christ : Carême 1881 - Monsabré, Jacques Marie Louis (Conférences de Notre-Dame de Paris, 1903)
Keywords: 2.Damage; Condition: Fair; Iglesia Católica Doctrinas; Religion; Teología dogmática

Exposition du dogme catholique: grace de Jésus-Christ : Carême 1883 - Monsabré, Jacques Marie Louis (Conférences de Notre-Dame de Paris, 1903)
Keywords: 2.Damage; Condition: Fair; Iglesia Católica Doctrinas; Religion; Teología dogmática

Raiz, 1898-1903 - Oliveira, António Correia de (França Amado, 1903)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor

Compendio de la Vida de la Venerable Madre Sor Geronimade La Asuncion - Perez, Lorenzo (The Philippine Publishing Co., 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Theologia Moral Universal - Rito, Conego J. M. (Companhia Portuguesa Editora, 1903)
Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

O Espirito do Veneravel Libermann - Rulhe, Joao A. (Typ. de J. M. de Sousa Cruz, 1903)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Catecismo da Doutrina Christa em Portuguez e Galoli - Silva Manuel M. Alves da (Typ. Noronha & CA., 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Anecdotes and Examples, Illustrating the Catholic Catechism - Spirago, Francis (Benziger Brothers, 1903)
Keywords: 1.Conservation 保護; Good

Sacra Liturgia - Stappen, J. F. Van der (Summi Pontificis, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Sacra Liturgia - Stappen, J. F. Van der (Summi Pontificis, 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃; Fair

Os Miseraveis - Victor Hugo (A. Ignacio dos Saintos, 1903)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover

Mois de Marie de N. D. de La Salette - Villard, R. P. (Librairie Bloud & cie., 1903)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Les Auteurs latins expliqués d'après une méthode nouvelle par deux traductions françaises: l une littérale et Juxtalinéaire présentant le mot Francais en regard des mots Latins correspondants l'autre correcte et précédé du texte Latin - Virgil (Librairie Hachette, 1903)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Laudatory poetry, Latin; Poésie élogieuse latine; languages

敬禮若瑟月 3巻 - Zottoli, Angelo (上海慈母堂活板重印, 1903)
敬禮若瑟月 3巻 晁徳蒞述 慈母堂, 光緒29 (1903) 封面四圍雙面界《1903年重生之主/尊少聖月/上海慈摩堂命盤套印》 信封背面寫著“眾神重生1868年。 格式：10 行，4 邊 30 個字符（16.9 x 10.4 厘米）
Keywords: Religion